Developing machine learning algorithms for meteorological temperature and humidity forecasting at Terengganu state in Malaysia - Hanoon M.S.; Ahmed A.N.; Zaini N.; Razzaq A.; Kumar P.; Sherif M.; Sefelnasr A.; El-Shafie A. (Nature Research, 2023)
air temperature; article; forecasting; linear regression analysis; multilayer perceptron; prediction; radial basis function; random forest; relative humidity; Terengganu